The Relationship between Political Ideology and Social Media Echo Chambers - Smith Namazzi, Smith Namazzi (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general purpose of this study was to explore the relationship between political ideology and social media echo chambers. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to political ideology and social media echo chambers. Preliminary empirical review revealed that echo chambers exist on social media platforms, with individuals predominantly exposed to information aligning with their political beliefs. Social Identity Theory and Selective Exposure Theory were instrumental in understanding how users' political affiliations influenced their interactions online, reinforcing echo chambers. These echo chambers, driven by users' desire for ingroup solidarity and selective exposure to like-minded content, posed challenges to democratic discourse and societal cohesion. The study emphasized the importance of addressing these challenges by promoting media literacy, critical thinking, and exposure to diverse viewpoints on social media platforms to foster a more inclusive and deliberative public sphere. Unique Contribution to Theory, Practice and Policy: The Social Identity theory, Selective Exposure theory and Dual Process theory may be used to anchor future studies on the relationship between political ideology and social media echo chambers. The study provided valuable recommendations that contributed to advancing theoretical understanding, informing practical interventions, and shaping policy responses to the challenges posed by echo chambers in contemporary political discourse. It emphasized the integration of social identity theory and selective exposure theory into theoretical frameworks, highlighting the psychological mechanisms driving the formation of echo chambers. Practically, the study underscored the importance of promoting media literacy and critical thinking skills among social media users, while suggesting that social media platforms play a pivotal role in shaping users' information environments. On the policy front, it emphasized the need for evidence-based interventions aimed at mitigating the adverse effects of echo chambers on democratic governance and societal cohesion.